Estudo químico de compostos pécticos obtidos dos frutos de Garcinia brasiliensis e avaliação de suas propriedades biológicas - Paiva, José Cezar De (2014)
Pectins are polymers mainly composed by unities of α-D galacturonic acids bonded by α- 1,4 links that are present in the plants cell wall. According to the branched composts in the main chain, a pectin can be divided in many kinds. Those polysaccharides have many complex structures, that are soluble in water and usually present low toxicity and have many uses in the chemical industry. This work aimed to extract, isolate and characterize the pectin composts present in the epicarps from the Garcinia brasilensis fruits, also known as bacupari. Two extraction methods were perfomed: one with water in a neutral solution and other with water in an acid one, both of them were heated. A comercial pectin from citrus was used to compare the analysis from the bacupari’s pectins. The pectin was obtained from residues of epicarp derived of routine and exaustive extractions with ethanol, that were realized at the Medical Phytochemistry and Chemistry Laboratory (MFCL). The process of pectin extraction in neutral aqueous solution resulted in a yield of 7,48% and the extraction process in the aqueous acid solution resulted in a yield of 6,15%. The pectin extracted from the g. brasiliensis fruit presented a high level of methoxylation and esterification and also showed higher phenolic content with more sequestring capacity of the DPPH free radical. Besides that, the antimicrobial and anti-inflammatory actvity were evaluated. The pectins extracted from the bacupari and the commercial one didn’t show a meaningfully activity agaisnt fungi and American Type Culture Collection (ATCC) standard bacterias, however they showed a considerable anti-inflammatory activity when compared to the indomethacin standard, which was tested on the carrageenan-induced paw edema in mices. Structural characterization, as well as data correlation of biological activity of natural and semi-sinthetic (acetylated) composts were performed, conducing to the development of new anti-inflammatory agents from the residues of the extraction of bacupari’s fruits.